2018
DOI: 10.1007/s11904-018-0378-z
|View full text |Cite
|
Sign up to set email alerts
|

HIV Persistence in Adipose Tissue Reservoirs

Abstract: Memory CD4 T cells and macrophages, the major host cells for HIV, accumulate in adipose tissue during HIV/SIV infection of humans and rhesus macaques. Whereas HIV and SIV proviral DNA is detectable in CD4 T cells of multiple fat depots in virtually all infected humans and monkeys examined, viral RNA is less frequently detected, and infected macrophages may be less prevalent in adipose tissue. However, based on viral outgrowth assays, adipose-resident CD4 T cells are latently infected with virus that is replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 132 publications
1
37
2
Order By: Relevance
“…The results presented here demonstrate that adipocytes have significant impact on ART distribution and activity within AT, which is newly believed to constitute a reservoir for latently infected HIV-/SIV-infected CD4 T cells (Couturier et al, 2015; Damouche et al, 2015; Couturier et al, 2016; Damouche et al, 2017; Hsu et al, 2017; Koethe et al, 2017; Couturier et al, 2018). In particular, these data suggest that adipocytes markedly diminish the antiretroviral effectiveness of NRTIs, particularly tenofovir, which constitutes an important “backbone” component of many antiretroviral regimens and is a first line agent for the treatment of HIV infection.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The results presented here demonstrate that adipocytes have significant impact on ART distribution and activity within AT, which is newly believed to constitute a reservoir for latently infected HIV-/SIV-infected CD4 T cells (Couturier et al, 2015; Damouche et al, 2015; Couturier et al, 2016; Damouche et al, 2017; Hsu et al, 2017; Koethe et al, 2017; Couturier et al, 2018). In particular, these data suggest that adipocytes markedly diminish the antiretroviral effectiveness of NRTIs, particularly tenofovir, which constitutes an important “backbone” component of many antiretroviral regimens and is a first line agent for the treatment of HIV infection.…”
Section: Discussionmentioning
confidence: 66%
“…They observed that NNRTI concentrations were significantly higher in AT lysates compared to PI concentrations, whereas N(t)RTIs were undetectable. Others and we have recently demonstrated that latently-infected CD4 T cells accumulate in AT and establish replication-competent reservoirs during chronic HIV infection, indicating the need for better understanding of antiretroviral pharmacology in AT (Couturier et al, 2015; Damouche et al, 2015; Couturier et al, 2016; Damouche et al, 2017; Hsu et al, 2017; Koethe et al, 2017; Couturier et al, 2018). …”
Section: Introductionmentioning
confidence: 93%
“…Latest data also provided evidence for a decreased NK cell number in mice orally infected with Salmonella Typhimurium, which also may contribute to an impaired susceptibility for infections in obese individuals (174). Interestingly, it has been proposed that selective therapeutic drugs might get trapped in adipose tissue in the treatment of HIV infections and, furthermore, immune cells, including NK cells, could be retained in adipose tissue, blocking their immunosurveillance elsewhere in the body (175).…”
Section: The Impact Of Obesity-related Altered Nk Cell Functionality mentioning
confidence: 99%
“…Lastly, the discovery of memory T cell accumulation in AT as a means of providing efficient secondary responses against pathogens constituted a major breakthrough; it became clear that AT is an immune partner in both local and systemic immune responses (Han et al, 2017; Figure 5). However, AT is a reservoir for pathogens in various infectious contexts (Nishimura et al, 2000;Neyrolles et al, 2006;Desruisseaux et al, 2007;Dhurandhar, 2011;Nagajyothi et al, 2012;Couturier et al, 2015Couturier et al, , 2016Damouche et al, 2015;Trindade et al, 2016;Beigier-Bompadre et al, 2017;Tanowitz et al, 2017;Couturier and Lewis, 2018;Contreras et al, 2019; Table 2). The detection of various bacterial DNAs in AT also constitutes an argument in favor of the tissue-specific microbiota hypothesis (Burcelin et al, 2013).…”
Section: Adipose Tissue and Infectionsmentioning
confidence: 99%